Native teacher and non-native teachers’ influence in the english teaching-learning process. a comparative study at the “Ramón Barba Naranjo” educative unit during the academic period september 2015- february 2016 - Meneses Sánchez, Lucia Jeaneth (2016)
This present research was focused on improving the Teaching- Learning Process in order that non-native English teachers develop new methodologies. The main problem was that the students did not pay attention and they did not work in English class and it makes the classes boring. Thus, they do not like the English language. Although that the non-native teachers have focused on teaching English language. There is a little inconvenience at the moment to teach to the students because the non-native teacher do not catch the attention of them due to the methodologies used by the non-native teachers do not give good results. That is the reason why, it has been considered a training course where it is important to find some activities to develop them….